Factors Affecting Purchase Decisions at the Equator Store Bengkulu City - Nurjana Nurjana; Oni Yulianti; Ermy Wijaya (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2022)
The purpose of this study was to determine the effect of location, image, price, service quality and product quality on purchasing decisions at the Equator Shop in Bengkulu City. The type of research used is a quantitative approach. The data analysis method used is multiple linear regression. The results of our study accept the hypothesis that there is a significant influence between the variables Location (X1), Image (X2), Price (X3), Quality of Service (X4) on Purchase Decisions (Y). It is known that the simultaneous test results show that the value of Fcount > Ftable is 12.877 > 2.22. When tested individually, all independent variables (Location, Image, Price, Quality of Service affect the Purchase Decision (Y).